Force sensing by the vascular protein von Willebrand factor is tuned by a strong intermonomer interaction - Müller, Jochen P. (Proc Natl Acad Sci U S A, 2016)
The large plasma glycoprotein von Willebrand factor (VWF) senses hydrodynamic forces in the bloodstream and responds to elevated forces with abrupt elongation, thereby increasing its adhesiveness to platelets and collagen. Remarkably, forces on VWF are elevated at sites of vascular injury, where VWF’s hemostatic potential is important to mediate platelet aggregation and to recruit platelets to the subendothelial layer. Adversely, elevated forces in stenosed vessels lead to an increased risk of VWF-mediated thrombosis. To dissect the remarkable force-sensing ability of VWF, we have performed atomic force microscopy (AFM)-based single-molecule force measurements on dimers, the smallest repeating subunits of VWF multimers. We have identified a strong intermonomer interaction that involves the D4 domain and critically depends on the presence of divalent ions, consistent with results from small-angle X-ray scattering (SAXS). Dissociation of this strong interaction occurred at forces above [Formula: see text] 50 pN and provided [Formula: see text] 80 nm of additional length to the elongation of dimers. Corroborated by the static conformation of VWF, visualized by AFM imaging, we estimate that in VWF multimers approximately one-half of the constituent dimers are firmly closed via the strong intermonomer interaction. As firmly closed dimers markedly shorten VWF’s effective length contributing to force sensing, they can be expected to tune VWF’s sensitivity to hydrodynamic flow in the blood and to thereby significantly affect VWF’s function in hemostasis and thrombosis.